Study on the Acoustic Emission Characteristics of Different Rock Types and Its Fracture Mechanism in Brazilian Splitting Test - Shengxiang, Li; Qin, Xie; Xiling, Liu; Xibing, Li; Yu, Luo; Daolong, Chen (Frontiers in Physics, 2021)
In order to investigate the relationship between rock micro-fracture mechanism and acoustic emission (AE) signal characteristic parameters under split loads, the MTS322 servo-controlled rock mechanical test system was employed to carry out the Brazilian split tests on granite, marble, sandstone and limestone, while FEI Quanta-200 scanning electron microscope system was employed to carry out the analysis of fracture morphology. The results indicate that that different scale of mineral particle, mineral composition and discontinuity all have influence on the fracture characteristics of rock, as well as the b-value . The peak frequency distribution of AE signal has obvious zonal features, and these distinct peak frequencies of four types of rock fall mostly in ranges of 0–100 kHz, 100–300 kHz, and above 300kHz. Due to the different rock properties and mineral compositions, the proportions of peak frequencies in these intervals are also different among the four rocks, which is also acting on b-value. In addition, for granite, the peak frequencies of AE signals are mostly distributed ,above 300 kHz for granite, marble and limestone，which mainly derive from the internal fracture of k-feldspar minerals ; for marble, the AE signals with peak frequency are mostly distributed in over 300 kHz, which mainly derive from the internal fracture of dolomite minerals and calcite minerals; AE signals for sandstone are mostly distributed in the range of 0-100 kHz, which mainly derive from the internal fracture of quartz minerals; for limestone, the AE signals with peak frequency are mostly distributed in over 300 kHz, which mainly derive from the internal fracture of granular- calcite minerals. The relationship between acoustic emission signal frequency of rock fracture and fracture scale is constructed through experiments, which is of great help for in-depth understanding of the scaling relationship of rock fracture.